2001
DOI: 10.1161/hc3601.093987
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Based Delivery of Sirolimus Reduces Neointimal Formation in a Porcine Coronary Model

Abstract: Background-The purpose of this study was to determine the efficacy of stent-based delivery of sirolimus (SRL) alone or in combination with dexamethasone (DEX) to reduce in-stent neointimal hyperplasia. SRL is a potent immunosuppressive agent that inhibits SMC proliferation by blocking cell cycle progression. Methods and Results-Stents were coated with a nonerodable polymer containing 185 g SRL, 350 g DEX, or 185 g SRL and 350 g DEX. Polymer biocompatibility studies in the porcine and canine models showed accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
391
3
15

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 624 publications
(433 citation statements)
references
References 29 publications
24
391
3
15
Order By: Relevance
“…[3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process. 6,7 Coating stents with antiproliferative agents allows targeted delivery to the region of local trauma. 8 A few studies have also shown similar reductions in in-stent restenosis with systemic administration of cell-cycle inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Mechanical disruption of the endothelium and media appears to trigger intimal and vascular smooth muscle proliferation around the stent surface, and borrowing from the oncologic armamentarium, cell-cycle inhibition has been shown to inhibit this process. 6,7 Coating stents with antiproliferative agents allows targeted delivery to the region of local trauma. 8 A few studies have also shown similar reductions in in-stent restenosis with systemic administration of cell-cycle inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…33 Previous studies of rapamycin-or everolimusimpregnated stents in animal models have shown that, compared to controls, local drug delivery inhibited within-stent stenosis or intimal hyperplasia by approximately 50%, but not much more. [34][35][36] Clinical trials with rapamycin-impregnated coronary stents have found within-stent restenosis to be nearly completely eliminated, indicating that atherosclerotic lesions may be more sensitive to rapamycin than normal animal arteries. 37 Human leukocytes are more sensitive to the antiproliferative effect of rapamycin than porcine leukocytes, 38 and the clearance of systemic rapamycin is slower in humans than in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies using coated stents that release rapamycin and paclitaxel have reported substantial decreases in the extent of in-stent restenosis during animal studies [8][9][10] and the initial phases of clinical trials. 11,12 However, coated stents could also be used to deliver genetic material to the cells of the vessel wall by diffusion from the polymer coating.…”
Section: Introductionmentioning
confidence: 99%